PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH PENDAU TAMBU KECAMATAN BALAESANG KABUPATEN DONGGALA - Rialdi, Muhammad; Suasa; Afandi, Muhammad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Public service is the provision of services or serving the needs of people or communities and organizations that have an interest in the organization, in accordance with the basic rules and procedures determined and aimed at providing satisfaction to service recipients. This study aims to find out the extent of health services at the Pendau Tambu Regional General Hospital, Balaesang District, Donggala Regency. The method used in this study is a qualitative approach with the Field Research method with a total of 5 informants. The data used consisted of secondary data obtained from Pendau Tambu Hospital, Balaesang District, Donggala Regency, as well as primary data obtained through direct observation and direct interviews with informants. Data analysis is carried out by data collection, data condensation, data display and conclusion drawing/verification. The results of the study show that services at Pendau Tambu Hospital, Balaesang District, Donggala Regency still encounter various obstacles. Starting with the encounter of problems in the Tangibles aspect , namely from the location of the hospital to the neatness of the employees in providing services, all of them experienced obstacles and were not optimal, and also the Realism aspect was still not optimal and encountered problems in the hospital, in the Responsiveness aspect it was quite satisfactory, while the Assurance aspectencountered a problem, namely that there was unclear information from the hospital to the patient, but for the education they had and the friendly nature had been maximized by the staff so that it could cause a feeling of security, and for Emphaty it was maximum. Therefore, this study suggests the need for a thorough evaluation and improvement from the Regional Government to the hospital, and the hospital needs innovation to improve the services of Pendau Tambu Hospital, Balaesang District, Donggala Regency in the future.